Meta-analysis of the association between toll-like receptor gene polymorphisms and hepatitis C virus infection - Du, Yuxuan; Li, Shumin; Wang, Xinyu; Liu, Jialu; Gao, Yan; Lv, Weimiao; Liu, Ping; Huang, Haiyan; Luan, Junwen; Zhang, Leiliang (Frontiers in Microbiology, 2023)
Objective: To investigate the association between Toll-like receptor (TLR) 3/7 gene polymorphisms and the infection by hepatitis C virus (HCV) Methods: Pubmed, Embase, Web of science, Scopus, CNKI, Wanfangdata and SinoMed were searched to identify studies focusing on the association between the TLR3 rs3775290 or the TLR7 rs179008 single nucleotide polymorphisms (SNPs) and the HCV infection. All the related articles from the inception of each database to January 15, 2023 were collected. Our meta-analysis was conducted, using the allelic model, the dominant model and the recessive model. Outcomes were presented by odds ratio (OR) and 95% confidence interval (95%CI). The heterogeneity across studies was assessed by the I2 test. A subgroup analysis was performed to explore the source of heterogeneity. Funnel plots were drawn to assess the risk of publication bias. Review Manager 5.4 was used for statistical analysis. Results: Ten articles were finally included, among which six studies were analyzed for rs3775290 and six studies were analyzed for rs179008. Studies relating to rs3775290 included 801 patients and 1045 controls, whereas studies relating to rs179008 included 924 patients and 784 controls. Results of meta-analysis showed that there is not a significant association between rs3775290 gene polymorphism and the infection by HCV (T vs C: OR=1.12, 95%CI 0.97~1.30; TT+CT vs CC: OR=1.20, 95%CI 0.73~1.96; TT vs CT+CC: OR=1.13, 95%CI 0.68~1.89). The recessive model showed that rs179008-T allele homozygotes had an 89% increased risk of an infection by HCV compared with rs179008-A allele carriers (TT vs AT+AA: OR=1.89, 95%CI 1.13~3.16). Results of the subgroup analysis demonstrated that the characteristics of the control population may serve as an important source of heterogeneity. In African populations, individuals with homozygous rs179008-T alleles had a higher risk of an infection by HCV than rs179008-A allele carriers (OR= 2.14, 95%CI 1.18~3.87). We did not find that this difference existed in European populations (OR=1.24, 95%CI 0.43~3.56). Conclusion: There is no significant association between rs3775290 single nucleotide polymorphism and the infection by HCV. Individuals with homozygous rs179008-T alleles have a higher risk of an infection by HCV than rs179008-A allele carriers, which is statistically significant in African populations.